Cannabinoid type-1 receptor signaling in central serotonergic neurons regulates anxiety-like behavior and sociability - Häring, Martin; Bartsch, Dusan (Frontiers in behavioral neuroscience, 2015)
The endocannabinoid system possesses neuromodulatory functions by influencing the release of various neurotransmitters, including γ-aminobutyric acid (GABA) and glutamate. A functional interaction between endocannabinoids and the serotonergic system has already been suggested. Previously, we showed that cannabinoid type 1 (CB1) receptor mRNA and protein are localized in serotonergic neurons of the raphe nuclei, implying that the endocannabinoid system can modulate serotonergic functions. In order to substantiate the physiological role of the CB1 receptor in serotonergic neurons of the raphe nuclei, we generated serotonergic (5-HT) neuron-specific CB1 receptor-deficient mice, using the Cre/loxP system with a tamoxifen-inducible Cre recombinase under the control of the regulatory sequences of the tryptophan hydroxylase 2 gene (TPH2-CreERT2), thus, restricting the recombination to 5-HT neurons of the central nervous system. Applying several different behavioral paradigms, we revealed that mice lacking the CB1 receptor in serotonergic neurons are more anxious and less sociable than control littermates. Thus, we were able to show that functional CB1 receptor signaling in central serotonergic neurons modulates distinct behaviors in mice.
Gesehen am 13.03.2018